2015
DOI: 10.1016/j.matbio.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

BMP-1/tolloid-like proteinases synchronize matrix assembly with growth factor activation to promote morphogenesis and tissue remodeling

Abstract: Bone morphogenetic protein-1 (BMP-1)/tolloid-like proteinases, here called BTPs, include the proteases originally identified for their roles in the C-terminal maturation of fibrillar procollagens ("procollagen C-proteinase"). Though numerous other substrates have since been discovered, the BTPs remain the main proteases involved in extracellular matrix assembly with little or no implication in matrix degradation. During the same period however, the BTPs have also become established as important proteases in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 109 publications
1
70
0
Order By: Relevance
“…Of note was the Smad4 effector gene which did show induction of expression, an observation that is in line with recent work on Hydra head regeneration [68]. Interestingly, the Tolloid gene ( Nve-Tld [81]), which encodes for an Astacin type metalloproteinase that has multiple substrates including the BMP2/4 antagonist Chordin [82], showed a shift in expression from high oral to aboral with time. However, when we examined BMP antagonist like genes, we found that while Chordin and Noggin orthologs had very low time course responses, kielin/chordin-like (KCP) [83], a gene whose product enhances BMP signaling, displayed high aboral expression.…”
Section: Resultssupporting
confidence: 67%
“…Of note was the Smad4 effector gene which did show induction of expression, an observation that is in line with recent work on Hydra head regeneration [68]. Interestingly, the Tolloid gene ( Nve-Tld [81]), which encodes for an Astacin type metalloproteinase that has multiple substrates including the BMP2/4 antagonist Chordin [82], showed a shift in expression from high oral to aboral with time. However, when we examined BMP antagonist like genes, we found that while Chordin and Noggin orthologs had very low time course responses, kielin/chordin-like (KCP) [83], a gene whose product enhances BMP signaling, displayed high aboral expression.…”
Section: Resultssupporting
confidence: 67%
“…Their experiment confirmed BMP1-like proteinases as essential proteins to the structure and wound healing of the skin. BMP1 proteinases are crucial for the formation of ECM not only by direct influence to its formation but also indirectly by activating TGF-β superfamily members including BMP-2 and BMP-4, profibrotic TGF-β1, and growth and differentiation factors GDF-8/-11 and IGF (24, 26). To date, there are seven different isoforms of the BMP1 protein (25).…”
Section: The Critical Role Of Myofibroblasts and Other Ecm Componentsmentioning
confidence: 99%
“…Such processing is involved in producing mature collagen monomers capable of assembling into fibrils. Subsequently, studies have expanded the list of proposed BTP substrates to include additional ECM-related proteins biosynthetically processed to their mature/functional forms [1, 3, 4]. These include lysyl oxidase, an enzyme necessary for covalent crosslinking of elastin and collagen fibrils [5]; collagens V and XI, and the small leucine-rich proteoglycans (SLRPs) decorin and biglycan [6-9], all of which play roles in regulating collagen fibrillogenesis [10] [11-13].…”
Section: Introductionmentioning
confidence: 99%